2013
DOI: 10.1073/pnas.1302676110
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 promotes motor neuron differentiation by collaborating with motor neuron-specific LIM complex

Abstract: The motor neuron (MN)-hexamer complex consisting of LIM homeobox 3, Islet-1, and nuclear LIM interactor is a key determinant of motor neuron specification and differentiation. To gain insights into the transcriptional network in motor neuron development, we performed a genome-wide ChIP-sequencing analysis and found that the MN-hexamer directly regulates a wide array of motor neuron genes by binding to the HxRE (hexamer response element) shared among the target genes. Interestingly, STAT3-binding motif is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 35 publications
5
64
1
Order By: Relevance
“…The STAT3 inhibitor significantly upregulated the expression of NF-200 and β-tubulin ш. A study has reported that IL-6 and the activity of its signaling partner establish a positive feedback mechanism with PAR1 that may promote IL-6-STAT3 signaling to levels sufficient to elicit fulminant astrogliosis, including increases in levels of the astroglial intermediate filament proteins GFAP and vimentin (18,19) In contrast to the current study, other studies have reported that STAT3 promotes motor neuron differentiation by collaborating with a motor neuronspecific LIM complex (21). STAT3 performs different roles during neural stem cell maintenance and motor neuron differentiation.…”
Section: Discussioncontrasting
confidence: 52%
“…The STAT3 inhibitor significantly upregulated the expression of NF-200 and β-tubulin ш. A study has reported that IL-6 and the activity of its signaling partner establish a positive feedback mechanism with PAR1 that may promote IL-6-STAT3 signaling to levels sufficient to elicit fulminant astrogliosis, including increases in levels of the astroglial intermediate filament proteins GFAP and vimentin (18,19) In contrast to the current study, other studies have reported that STAT3 promotes motor neuron differentiation by collaborating with a motor neuronspecific LIM complex (21). STAT3 performs different roles during neural stem cell maintenance and motor neuron differentiation.…”
Section: Discussioncontrasting
confidence: 52%
“…These studies, combined with MN transcriptome analyses (Lee et al, 2012;Mazzoni et al, 2013), revealed that the ISL1-LHX3 complex directly regulates the expression of a wide range of downstream effector genes that function not only in cell fate specification but also in subsequent maturation steps of MN differentiation, such as cell migration, axon pathfinding and synapse formation. As a result, the roles of individual target genes of the ISL1-LHX3 complex in MN specification and differentiation/maturation have finally begun to be dissected (Cho et al, 2014;Lee et al, 2012Lee et al, , 2013Mazzoni et al, 2013). Interestingly, v-MNs in embryos deficient in both LHX3 and LHX4 reorients their axonal projections dorsally, whereas the misexpression of LHX3 in d-MNs reorients their axonal projections ventrally (Sharma et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…LIM homeobox 3 (LHX3) and Islet 1 (ISL1), two LIMhomeodomain (LIM-HD) factors, play crucial roles in directing MN fate specification and differentiation in developing spinal cord (Lee et al, 2013;Pfaff et al, 1996;Sharma et al, 1998;Tanabe et al, 1998;Thaler et al, 2002). During these processes, two ISL1: LHX3 dimers bind to nuclear LIM interactor (NLI; also known as LDB for LIM-domain binding), which has a self-dimerization domain, and form a hexameric complex, named the ISL1-LHX3 complex ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations